Analysis of Fungal Communities of High-temperature and Medium-temperature Daqu in Binzhou Region and Their Correlation with Sensory Quality - Huijun ZHAO; Yurong WANG; Qiangchuan HOU; Haibo ZHANG; Hui NI; Mingbo YE; Zhuang GUO (Shipin gongye ke-ji)
To analyze the differences in fungal community structure and sensory quality of different types of Daqu in Binzhou, Shandong Province, the fungal community structure and quality characteristics of high-temperature and medium-temperature Daqu in Binzhou region were comprehensively analyzed by high-throughput sequencing, electronic nose and electronic tongue technology. The results showed that the diversity and richness of fungal species in high-temperature Daqu were significantly lower than those in medium-temperature Daqu (P<0.01), and there were significant differences in fungal community structure between the two types of Daqu (P<0.05). Among them, the average relative abundance of Thermomyces in high-temperature Daqu was significantly higher (P<0.05), while the average relative abundance of Aspergillus, Rhizopus, Rhizomucor, and Lichtheimia in medium-temperature Daqu were significantly higher (P<0.05). Thermomyces and Wickerhamomyces could be used as biomarkers for high-temperature and medium-temperature Daqu, respectively. And the stability of fungal microbial network in high-temperature Daqu was weaker than that in medium-temperature Daqu. In addition, there was no significant difference in flavor quality between the two types of Daqu (P>0.05), but the difference in taste quality was significant (P<0.01). Among them, the bitterness and umami-aftertaste were significantly lower in high-temperature Daqu (P<0.05), and the sourness, saltiness and bitterness-aftertaste were significantly lower in medium-temperature Daqu (P<0.05). And there was no significant correlation between the dominant fungal genera of Daqu and flavor indexes (P>0.05), but there was a significant correlation between the dominant fungal genera of Daqu and taste indexes (P<0.01). Among them, Thermomyces was positively correlated with sourness, astringency and bitterness-aftertaste and negatively correlated with umami and umami-aftertaste, while Aspergillus, Rhizopus, Rhizomucor, Rasamsonia, and Lichtheimia were the opposite. It can be seen that there were differences in fungal community structure and taste quality between high-temperature and medium-temperature Daqu in Binzhou region, and there was a correlation between dominant fungal genera and taste index.